Enhanced charge separation and interfacial charge transfer of InGaN nanorods/C3N4 heterojunction photoanode. (20th November 2019) - Xu, Zhenzhu; Zhang, Shuguang; Gao, Fangliang; Gao, Peng; Yu, Yuefeng; Lin, Jing; Liang, Jinghan; Li, Guoqiang
Abstract: Semiconducting heterostructures designed with rational engineering of energy bands and interfaces can accelerate electron-hole separation to boost photoelectrochemical (PEC) water splitting. Herein, InGaN nanorods (NRs)/C3 N4 heterojunction photoanode has been constructed by directly loading C3 N4 on the InGaN NRs surface through a simple chemical vapor deposition method. The working principles and interfacial charge kinetics of the heterojunction have been proposed. The unique heterojunction exhibits efficient charge separation through the potential gradient and enhanced interfacial charge transfer due to the surface passivation. Eventually, the photocurrent density of the InGaN NRs/C3 N4 heterojunction photoanode with loading weight ratio of 0.38% reaches up to 13.9 mA/cm 2 at 1.23 V vs. RHE under an illumination of ∼100 mW/cm 2, which is 2 times higher than that of the pristine InGaN NRs. The applied bias photon-to-current efficiency of the designed heterojunction can achieve as high as 2.26% at 0.9 V vs. RHE, 1.65 times higher than the bare InGaN NRs (1.37%). Moreover, the InGaN NRs/C3 N4 heterojunction exhibits an obviously improved stability against photocorrosion due to the efficient interfacial charge transfer. This work can open up a novel route for the rational design and construction of heterojunction based photoelectrode to readily enhance the PEC performance.